Achieving high strength and deformability in a high entropy alloy containing the multiscale phase structure. (December 2022) - Zhao, Y.; Fu, X.; Lu, Y.; Yu, Q.
Abstract: Hard intermetallic phases have been widely introduced into alloys to strengthen the materials, while their low deformability usually results in severe stress concentration at the phase boundaries which is detrimental to ductility. Here an Al0.4 CoCrFeNi alloy with a multiscale phase structure was synthesized, in which the B2 intermetallic phase that contains solid solution nanoparticles with body-centered cubic structure, is embedded in a face-centered cubic matrix. With such structure, the material displays enhanced strength and deformability simultaneously. The existence of B2 phase significantly contributes to materials' strength, while the body-centered cubic nanoparticles play an important role in releasing and dispersing the stress concentration at the B2 and face-centered cubic interface. The results give insight into multiphase design for high performance alloys. Graphical abstract: Image 1 Highlights: The multi-scale phase structure is designed in high entropy alloys Al0.4 CoCrFeNi. The special structure plays important roles in promoting strength and deformability simultaneously. Nanoparticles of body-centered cubic solid solution embedded in B2 and distributed along B2/face-centered cubic interphase facilitated the release of stress concentration and promoted dislocation slip in multiple directions.